Obstetric Management of COVID-19 in Pregnant Women - Mei, Youwen; Luo, Dan; Wei, Sumei; Liao, Xiaoyan; Pan, Yue; Yang, Xiao; Lin, Yonghong (Frontiers in Microbiology, 2020)
The 2019 novel coronavirus disease (COVID-19), which is caused by the novel beta coronavirus, SARS-CoV-2, is currently prevalent all over the world, causing thousands of deaths with relatively high virulence. Like two other notable beta coronaviruses, severe acute respiratory syndrome coronavirus-1 (SARS-CoV-1) and Middle East respiratory syndrome coronavirus (MERS-CoV), SARS-CoV-2 could lead to severe contagious respiratory disease. Due to impaired cellular immunity and physiological changes, pregnant women are susceptible to respiratory disease and they are more likely to develop severe pneumonia. Given the prevalence of COVID-19, it is speculated that some pregnant women have already been infected. However, limited data are available for the clinical course and management of COVID-19 in pregnancy. Therefore, we conducted this review to identify strategies for the obstetric management of COVID-19. We compared the clinical course and outcomes of COVID-19, SARS, and MERS in pregnancy and discussed several drugs for the treatment of COVID-19 in pregnancy.